2019
DOI: 10.1038/s41419-019-2036-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial 3243A > G mutation confers pro-atherogenic and pro-inflammatory properties in MELAS iPS derived endothelial cells

Abstract: Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) syndrome is a mitochondrial disorder that is commonly caused by the m.3243A > G mutation in the MT-TL1 gene encoding for mitochondrial tRNA(Leu(UUR)). While clinical studies reported cerebral infarcts, atherosclerotic lesions, and altered vasculature and stroke-like episodes (SLE) in MELAS patients, it remains unclear how this mutation causes the onset and subsequent progression of the disease. Here, we report that in addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 46 publications
0
32
3
Order By: Relevance
“…Safety and efficacy of sonlicromanol, the parent compound of KH176m, was evaluated in a phase 1 randomized control trial (RCT) in healthy volunteers 1 and a Phase 2a RCT 4 in patients with mitochondrial m.3243A > G spectrum disorder. Of importance, MELAS iPS derived endothelial cells show both pro-atherogenic and pro-inflammatory properties 45 . Our phase 1 and 2a studies revealed that sonlicromanol had an acceptable safety profile and favorable pharmacokinetics, was well tolerated over a treatment period of 28 days, and had a positive effect on cognition, an important burden for patients with mitochondrial disease.…”
Section: Discussionmentioning
confidence: 99%
“…Safety and efficacy of sonlicromanol, the parent compound of KH176m, was evaluated in a phase 1 randomized control trial (RCT) in healthy volunteers 1 and a Phase 2a RCT 4 in patients with mitochondrial m.3243A > G spectrum disorder. Of importance, MELAS iPS derived endothelial cells show both pro-atherogenic and pro-inflammatory properties 45 . Our phase 1 and 2a studies revealed that sonlicromanol had an acceptable safety profile and favorable pharmacokinetics, was well tolerated over a treatment period of 28 days, and had a positive effect on cognition, an important burden for patients with mitochondrial disease.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that impaired housekeeping of ROS may be linked to RCC and MELAS. In accord with these data, it was found that antioxidant treatments alleviate MELAS manifestations ( Pek et al., 2019 ). Furthermore, SOD2 interaction with the amyloid precursor protein (APP; Figure 1 D) was found to be connected to mt-controlled ROS and APP processing, an otherwise altered phenomenon in brain diseases mediated by RCC deficiency ( Area-Gomez et al., 2018 ; Wilkins and Swerdlow, 2017 ).…”
Section: A Human Mt Protein Connectome Perspective In Rdsmentioning
confidence: 54%
“…In dysfunctional endothelial cells, more monocytes adhered to endothelial cells than in control cells, suggesting an atherosclerosis-like pathology in MELAS [12]. Notably, these pathological findings could be reversed by treatment with antioxidants, suggesting that lowering ROS is crucial for MELAS patients [12]. In a study by Tanaka et al (2004), the mtDNA variant m.8794T>C in ATP6 was associated with coronary sclerosis [13].…”
Section: Primary Mitochondrial Asclmentioning
confidence: 98%
“…The heteroplasmy rates were neither influenced by classical risk factors for ASCL nor by any clinical parameter [11]. In a recent study on endothelial cells from patients with MELAS due to the variant m.3243A>G, it was found that endothelial cells were diseased and found to be pro-atherogenic and pro-inflammatory due to high levels of reactive oxygen species (ROS), OxLDLs, and a high basal expression of vascular cell adhesion molecule-1 (VCAM-1), particularly isoform-b [12]. In dysfunctional endothelial cells, more monocytes adhered to endothelial cells than in control cells, suggesting an atherosclerosis-like pathology in MELAS [12].…”
Section: Primary Mitochondrial Asclmentioning
confidence: 99%
See 1 more Smart Citation